2021
DOI: 10.1371/journal.pone.0248245
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of asymptomatic malaria infection in pregnant women in Sub-Saharan Africa: A challenge for malaria elimination efforts

Abstract: Background In Sub-Saharan Africa (SSA), where malaria transmission is stable, malaria infection in pregnancy adversely affects pregnant women, fetuses, and newborns and is often asymptomatic. So far, a plethora of primary studies have been carried out on asymptomatic malaria infection in pregnant women in SSA. Nevertheless, no meta-analysis estimated the burden of asymptomatic malaria infection in pregnant women in SSA, so this meta-analysis was carried out to bridge this gap. Methods PubMed, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 47 publications
4
41
3
1
Order By: Relevance
“…Besides this, prime gravidae had increased odds of malaria infection compared to the multigravid. Similar results were found from studies done in sub-Saharan Africa countries [24][25][26][27], which showed a higher risk of malaria infection among primigravidae than multigravidae. Low risk of malaria among multigravidae mothers may be associated with the development of preimmunity to malaria with increased gravidity and previous exposures.…”
Section: Discussionsupporting
confidence: 89%
“…Besides this, prime gravidae had increased odds of malaria infection compared to the multigravid. Similar results were found from studies done in sub-Saharan Africa countries [24][25][26][27], which showed a higher risk of malaria infection among primigravidae than multigravidae. Low risk of malaria among multigravidae mothers may be associated with the development of preimmunity to malaria with increased gravidity and previous exposures.…”
Section: Discussionsupporting
confidence: 89%
“…Further, P. falciparum is accountable for most of the malaria-related deaths worldwide, estimated at about 409,000 deaths arising from approximately 229 million cases of malaria in 2019, as reported by the World Health Organization (WHO) 5 . Children under five years and pregnant women are among the most vulnerable group affected by malaria 1 , 5 – 7 . An obligatory step of infection by malaria parasites starts with the clinically silent liver-stage infection, wherein Plasmodium sporozoites, delivered by female Anopheles mosquitoes invade hepatocytes and replicate inside a parasitophorous vacuole, inside the hepatic host cell.…”
Section: Introductionmentioning
confidence: 99%
“…We noted that first pregnancy women were at higher risk of malaria and STI/RTI coinfections. The high susceptibility of primigravid women to malaria [ 10 ], combined with the high prevalence of STI/RTI reported in the current study increased the risk of malaria and STI/RTI coinfection. Therefore, it would be more effective to systematically screen and treat this population or explore alternative combination drug that can prevent malaria infection and adequately treat STI/RTI without the need of diagnostic.…”
Section: Discussionmentioning
confidence: 77%
“…Another study estimated that 38% of Zambian pregnant women were coinfected with malaria and at least one STI/RTI [8]. Pregnant women, despite their high susceptibility to infections in SSA are usually asymptomatic, which severely limits clinical detection and appropriate case management [9][10][11].…”
Section: Tropical Medicine and Healthmentioning
confidence: 99%